Isoflurane Impacts Murine Melanoma Growth in a Sex-Specific, Immune-Dependent Manner: A Brief Report. (June 2018) - Meier, Angela; Gross, Emilie T. E.; Schilling, Jan M.; Seelige, Ruth; Jung, Yujin; Santosa, Endi; Searles, Stephen; Lin, Tuo; Tu, Xin M.; Patel, Hemal H.; Bui, Jack D.
Abstract : The impact of volatile anesthetics on cancer progression has been observed for decades, but sex differences have not been described. Male and female immune systems vary considerably, and the immune system plays an important role in limiting cancer growth. Currently, mouse models describing the impact of volatile anesthetics on cancer growth are limited to same-sex models. In this brief report, we describe a sex-specific impact of isoflurane on melanoma growth observed in wild-type but not in immune-deficient mice. Future experimental designs related to anesthesia and cancer should evaluate the biological variable of sex in a systematic manner.